THE ROLE OF FAST FASHION CONSUMPTION PATTERNS IN MEDIATING SELF-CONGRUITY AND BRAND IMAGE ON PURCHASING DECISIONS - Makitta Widi Samudra (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The fast fashion industry emerged at the end of the 20th century in response to consumers' desire to get clothes with the latest trends at affordable prices. The tendency of consumptive patterns and changes in trends that change quickly led to the emergence of the concept of ready to wear, namely fast fashion. This study aims to examine the role of consumption patterns in mediating self-congruity and brand image on purchasing decisions. Self-congruity is self-conformity to the brand. Then brand image is a consumer perception formed from information obtained about the brand. This research is descriptive quantitative and uses non-probability purposive sampling techniques. The sample in this study was customers of fast fashion products and amounted to 120 people. Data was collected using an online questionnaire with likert scale and processed using partial least square analysis techniques. The tool for processing data in this study is SEM-PLS 3.0 Software. The results of this study are self-congruity and brand image affect purchasing decisions and consumption patterns. Then consumption patterns are able to mediate self-congruity and brand image on purchasing decisions.